2022
DOI: 10.1038/s41598-022-26446-x
|View full text |Cite
|
Sign up to set email alerts
|

In silico activity and ADMET profiling of phytochemicals from Ethiopian indigenous aloes using pharmacophore models

Abstract: In silico profiling is used in identification of active compounds and guide rational use of traditional medicines. Previous studies on Ethiopian indigenous aloes focused on documentation of phytochemical compositions and traditional uses. In this study, ADMET and drug-likeness properties of phytochemicals from Ethiopian indigenous aloes were evaluated, and pharmacophore-based profiling was done using Discovery Studio to predict therapeutic targets. The targets were examined using KEGG pathway, gene ontology an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 70 publications
(88 reference statements)
0
5
0
Order By: Relevance
“…From the results, most of the compounds were not OCT2 substrates, entailing a lower chance of drug-herbal interaction through this mechanism. Bultum et al also evaluated plant extracts that contained compounds found in M. crassa , palmitic acid and methyl palmitate, and the ADME results were favourable for drug development benchmarks 86 . Therefore, many compounds in the M. crassa extract can be taken further for drug development.…”
Section: Discussionmentioning
confidence: 99%
“…From the results, most of the compounds were not OCT2 substrates, entailing a lower chance of drug-herbal interaction through this mechanism. Bultum et al also evaluated plant extracts that contained compounds found in M. crassa , palmitic acid and methyl palmitate, and the ADME results were favourable for drug development benchmarks 86 . Therefore, many compounds in the M. crassa extract can be taken further for drug development.…”
Section: Discussionmentioning
confidence: 99%
“…was accessed on a web server that displays the chemical information of the resource. Canonical Simplified Molecular Input Line Entry System (SMILES) and their biological activities were obtained by entering the chemical names of small molecules reported in A.M. 12 .…”
Section: Methodsmentioning
confidence: 99%
“…The prediction of physicochemical properties contributes to estimating drug capacity to cross the biological barriers. The widely used molecular descriptor in drug transport properties, TPSA (topological polar surface area) is the summation of the molecular surface area of polar atoms such as nitrogen, oxygen, and their attached hydrogens 12,13 .…”
Section: Swissadmementioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that in silico investigations are a rapid and cost-effective medium for screening plant-derived bioactive compounds with therapeutic activity using a computational biology approach to discover new drugs and inhibitors (small molecules or ligands) against potential molecular targets of the SARS-CoV-2 virus (Bultum et al 2022). In some cases, certain drugs have been repurposed using a virtual screening approach to target SARS-CoV-2 viral proteases, with Paxlovid (nirmatrelvir-ritonavir), molnupiravir and remdesivir being approved by the Food and Drug Administration (FDA) for the treatment of hospitalised COVID-19 patients, particularly adults and children (Kushari et al 2022; Umadevia et al 2020).…”
Section: Introductionmentioning
confidence: 99%